Evaluation of Colour Changed of Acrylic Resin Materials in the Different Solutions - Yesil Duymus, Zeynep; Yanikoglu, Nuran; Arik, Mustafa (Asian Journal of Chemistry, 2010)
Colour stability of acrylic resin materials for denture base is important in their clinical performance. Present study evaluated the effect of material testing surface (rough and smooth), polymerization techniques (heat and auto-polymerized) and different solutions (coffee, tea, Turkish coffee, mouth wash and distilled water) on the colour stability of two acrylic resin materials. Thirty disks of each material (50 mm × 0.5 mm) were prepared. The specimens of each material were divided in two groups. The first groups were abraded with silicon carbide paper. The second groups were polished with pumice and white diamond. Twenty-four specimens were evaluated before and after 1, 7 and 30 days of immersion in different staining solutions and distilled water. Six specimens were evaluated before and after 6, 12 and 24 h of immersion in mouth wash. Colour changes were monitored by using the UV/vis/NIR spectrophotometer. As a results, material testing surface, staining solutions and immersion time were significant factors that affected the colour stability (p < 0.001). The auto-polymerized acrylic resin specimens showed high levels of colour changes in Turkish coffee. The heat polymerized acrylic resin materials were more colour stable than auto-polymerized acrylic resin specimens.